Digital Zakat and the Role of Zakat Intermediation: Case Study at BAZNAS West Java - Fadilah, Sri; Rosdiana, Yuni; Sundaya, Yuhka; Maemunah, Mey; Fitriah, Epi; Lestari, Rini; Hernawati, Nopi (KnE Social Sciences, 2024)
This study aims to determine the relationship between the use of digital zakat and the intermediary role of zakat in zakat institutions. The background of the research starts from the zakat institution which is authorized by the government according to Law Number 23 of 2011 concerning the management of zakat in Indonesia which carries out the role of zakat intermediary, namely collecting funds from muzaki and distributes to mustahiq. In fact, there is less than optimal collection of zakat with low realization of collection and less effectiveness of zakat distribution. Allegedly many factors are considered to be the cause of the ineffectiveness of the intermediary role of zakat, namely the collection and distribution of zakat. In this article, it is explained that the implementation of digital zakat is considered as one of the factors that has become an obstacle. The research method used is a case study at zakat institutions at the provincial level in the city of Bandung, namely BAZNAS West Java. Variables of research are digital zakat and the role of intermediation. Data collection were done by performing interviews and documentation. The results of the study show that the implementation of digital zakat at zakat institutions can optimize zakat collection with evidence of increased collection and more effective distribution of zakat, especially related to performance achievements. Keywords: digital zakat, effectiveness, optimization of collection